An Optimum Financing Scheme for Baseload Thin-film and Monocrystalline PV Plants in Indonesia - Arifin, Zainal; Septiyanthy, Ria; Alkano, Desti; Jufri, Fauzan Hanif; Sudiarto, Budi (International Journal of Energy Economics and Policy, 2021)
This paper investigates the most optimum financing scheme for medium-scale grid-connected PV plant investments in Indonesia. Eleven (11) financing schemes, composed through the combination of Viability Gap Fund (VGF), international grant, tax incentives, and low loan interest, are studied. The electricity tariff resulted from each financing scheme is analyzed and compared to the applicable feed-in tariff to find the optimum financing scheme. Moreover, this paper also includes two types of PV modules, such as thin-film and monocrystalline. The result shows that the funding combination consists of 50% of capital expenditure (CAPEX) from VGF provided by the Government of Indonesia (GoI), 30% of CAPEX provided by the international grant, and 5% of loan interest results in the optimum financing scheme. The resulting electricity tariffs from this financing scheme are 571.04 IDR/kWh and 761.76 IDR/kWh for thin-film and monocrystalline PV plants, respectively, which is below the lowest existing feed-in tariff (985 IDR/kWh). Keywords: Thin-film PV, Monocrystalline PV, feed-in tariff, economic feasibility, financing scheme JEL Classifications: P41, P43, P49 DOI: https://doi.org/10.32479/ijeep.11387